2010
DOI: 10.1021/bm1001813
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharide Gels Based on Chitosan and Modified Starch: Structural Characterization and Linear Viscoelastic Behavior

Abstract: We investigated the properties of polymeric systems formed by cross-linking chitosan with modified starch (oxidized maltodextrin). Such a macromolecular cross-linker proved to be efficient to react with chitosan with potentially minimal toxicity. The structural characterization of modified starch alone and of the two-polysaccharide reactive systems was performed using (1)H NMR and FTIR. The rheological behaviors of all systems, from solutions to gels, were also characterized. Depending on experimental paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 41 publications
3
53
0
1
Order By: Relevance
“…The peak at 2925 cm À1 was the characteristic peak in the Schiff base. 29 In addition, the characteristic peak of chitin at 1565 cm À1 (amide II) disappeared in the hydrogel. FT-IR demonstrated that the aldehyde groups in ADA50 were combined with amine groups in AMC7 by Schiff base.…”
Section: Resultsmentioning
confidence: 98%
“…The peak at 2925 cm À1 was the characteristic peak in the Schiff base. 29 In addition, the characteristic peak of chitin at 1565 cm À1 (amide II) disappeared in the hydrogel. FT-IR demonstrated that the aldehyde groups in ADA50 were combined with amine groups in AMC7 by Schiff base.…”
Section: Resultsmentioning
confidence: 98%
“…The observed frequencies in the range of 1500-1200 cm À1 are assigned to the coupled modes of vibration that involves C-H bending [1]. In the region of 1200-1000 cm…”
Section: Soluble Oxidized Starch-fe(iii) Complexmentioning
confidence: 93%
“…Starch is a natural carbohydrate with several benefits: It is non-toxic, biodegradable, abundantly available, and contains various possibilities for modification [1][2][3]. Starch has a granular structure [4], which consists of linear amylose and branched amylopectin [5] structured from anhydroglucose units (AGUs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the spectrum of starch, the absorption bands in the region of 700-1000 cm −1 are due to atomic group involved in the anomeric form [22], in the region of 1000-1200 cm −1 are due to stretching vibration of C O, and in the region of 1200-1500 cm −1 are related to C H bending [23]. The absorption bands in regions of 2800-3000 cm −1 and 3300-3500 cm −1 are assigned to C H and O H stretching, respectively.…”
Section: Synthesis and Characterization Of St-gtmacmentioning
confidence: 99%